2018
DOI: 10.31235/osf.io/msvqh
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Till Data Do Us Part: Understanding Data-Based Value Creation in Data-Intensive Infrastructures

Abstract: Much of the literature on value creation in social media-based infrastructures has largely neglected the pivotal role of data and their processes. This paper tries to move beyond this limitation and discusses data-based value creation in data-intensive infrastructures, such as social media, by focusing on processes of data generation, use and reuse, and on infrastructure development activities. Building on current debates in value theory, the paper develops a multidimensional value framework to interrogate the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…), genomic databases (e.g. Singh ) and biomedical data platforms (Tempini ) that have demonstrated how these infrastructures are sites of multiple processes of valuation and valourisation – including economic, epistemic and social values (e.g. related to identity building and shared sociality).…”
Section: Valuing and The Biopolitics Of Ucb Collectionmentioning
confidence: 99%
“…), genomic databases (e.g. Singh ) and biomedical data platforms (Tempini ) that have demonstrated how these infrastructures are sites of multiple processes of valuation and valourisation – including economic, epistemic and social values (e.g. related to identity building and shared sociality).…”
Section: Valuing and The Biopolitics Of Ucb Collectionmentioning
confidence: 99%
“…Barrett, Oborn, and Orlikowski (2016) identified six different types of value that different stakeholders gained from interacting on an online health community platform -financial, epistemic, ethical, service, reputational, and platform. However, Tempini (2017) notes data reuse to enhance one stakeholder group's value may make data less valuable to others, because the processes of data generation, use, and reuse, and infrastructure development activities are not easily separated. Moreover, shifting data from one context to another may lessen value for some stakeholders.…”
Section: Forms Of Phi Data Governancementioning
confidence: 99%
“…These values are not necessarily contradictory, but data use and reuse is not seamless (Tempini 2017). Dr. Julian Huppert, head of an Independent Review Panel instituted by DMH to provide independent oversight and ensure public accountability for its health endeavors, noted that the NHS PHI data were not as optimized for reuse as DMH had expected: "DeepMind could use AI to help with healthcare, but I think that it found that the state of data in the NHS was not as good as it had hoped so it had to step back from this" (Wakefield 2017, 12).…”
Section: Value In the Phi Datamentioning
confidence: 99%
“…He collaborated with most of the employees on site, and corroborated the observational and documental material with focused interviews for a total of 30 hours of recording. Some of this ethnographic research has been published as peer-reviewed articles before, but these works did not deal with the issues this article is concerned with (Kallinikos & Tempini, 2014;Tempini, 2015Tempini, , 2017. 8 Scraping is a technical term for the extraction of data from a raw html source, i.e.…”
Section: Codamentioning
confidence: 99%